Antidiabetic potential: In vitro inhibition effects of bromophenol and diarylmethanones derivatives on metabolic enzymes. Issue 12 (27th November 2018) - Demir, Yeliz; Taslimi, Parham; Ozaslan, Muhammet Serhat; Oztaskin, Necla; Çetinkaya, Yasin; Gulçin, İlhami and Beydemir, Şükrü and Goksu, Suleyman
Abstract: Aldose reductase converts glucose to sorbitol in the polyol pathway. It is an important enzyme to prevent diabetic complications. In this study, we studied the inhibitory effects of bromophenol derivatives on aldose reductase (AR), α‐glucosidase, and α‐amylase enzymes. In the bromophenols series, compound1f showed the maximum inhibition effect against AR with a K i value of 0.05 ± 0.01 μM, while compound1d showed the lowest inhibition effect against AR with a K i value of 1.13 ± 0.99 μM. In addition, α‐amylase from porcine pancreas and α‐glucosidase from Saccharomyces cerevisiae were used as enzymes. In this study, all compounds were tested for the inhibition of the α‐glucosidase enzyme and demonstrated efficient inhibition profiles with K i values in the range of 43.62 ± 5.28 to 144.37 ± 16.37 nM against α‐glucosidase. Additionally, these compounds were tested against the α‐amylase enzyme, which determined an effective inhibition profile with IC50 values in the range of 9.63–91.47 nM. These compounds can be selective inhibitors of AR, α‐glucosidase, and α‐amylase enzymes as antidiabetic agents. Abstract : The effects of bromophenol derivatives on aldose reductase (AR), α‐glucosidase, and α‐amylase were investigated. In the bromophenols series, compound1f showed the highest inhibition effect against AR ( K i = 0.05 ± 0.01 μM) and1d showed the lowest effect ( K i = 1.13 ± 0.99 μM). All tested compounds also showed inhibition of α‐glucosidase and α‐amylase. Thus, these compounds have potential as antidiabetic agents.